The STING antagonist H‐151 ameliorates psoriasis via suppression of STING/NF‐κB‐mediated inflammation. (30th October 2021) - Pan, Yanhong; You, Yanping; Sun, Li; Sui, Qibang; Liu, Liu; Yuan, Haoliang; Chen, Caiping; Liu, Jun; Wen, Xiaoan; Dai, Liang; Sun, Hongbin
Abstract : Background and Purpose: Psoriasis is a chronic inflammatory skin disease associated with both innate and adaptive immune responses. The stimulator of interferon genes (STING) protein engages in sensing of cytosolic DNA to initiate dsDNA‐driven immune responses. In vitro and in vivo anti‐psoriasis effects of STING antagonist H‐151 were explored. Experimental Approach: We analysed the gene expression profile of STING and related downstream targets in the skin samples of healthy people and psoriasis patients from the GEO database. Cellular inhibitory activity of H‐151 on STING pathway was confirmed via qPCR and western blotting. The preventive effect of topical application of H‐151 on imiquimod‐induced psoriatic mice was examined through histological, immunohistochemical, immunofluorescent, flow cytometric analysis, ELISA Kits and other approaches. Preliminary mechanistic studies were also performed. Key Results: Gene expressions of STING and its downstream target were up‐regulated in lesional skin samples from psoriasis patients. Topical administration of H‐151 attenuated the skin lesions in imiquimod‐induced psoriatic mouse model, while the secretion of pro‐inflammatory cytokines (IL‐17, IL‐23 and IL‐6), infiltration of M1 macrophages and differentiation of Th17 cells were significantly suppressed by H‐151 treatment. Mechanistically, H‐151 inhibited STING/NF‐κB signalling in both keratinocytes and immune cells. Conclusion and Implications: H‐151 displayed anti‐inflammatory activity in both keratinocytes and immune cells, and decreased the severity of psoriatic response in vivo. Inhibition of STING signalling pathway may represent a novel therapeutic approach to psoriasis and related complications.